A Novel Di(6‐aminouracil‐5‐yl)‐arylmethane Derivative as Fluorescence Ratiometric Chemodosimeter for Mercury Detection in Aqueous Solution. Issue 14 (9th September 2016) - Dhaka, Gargi; Thakur, Meghna; Singh, Jasvinder; Kumar, Subodh; Kaur, Navneet
Abstract: The reaction of quinolone aldehyde with aminouracil resulted in formation of probe2, which acted as chemodosimeter for Hg 2+ and chemosensor for CN − ion in buffered aqueous solution. Addition of Hg 2+ ions to2 prompted its cyclocondensation leading to formation of3 . This induced a remarkable change in the emission spectrum, enabling ratiometric fluorescent sensing of Hg 2+ in aqueous media. Evidences for this cyclocondensation were provided by fluorescence spectra and especially 1 H NMR and HRMS experiments. Also, presence of two free –NH2 groups enabled2 to act as efficient chemosensor for CN − in aqueous media. Furthermore, test strips containing the sensor molecule were easily fabricated and provided a low‐cost, practical and efficient test kit for Hg 2+ ions. Probe2 also showed antibacterial activity against both gram‐positive ( Staphylococcus aureus ) and gram‐negative ( Escherichia coli ) bacteria. Abstract : The attack of Hg 2+ prompted cyclocondensation of di(uracilyl) derivative (2) to closed cyclic ring structure (3 ). Chemodosimeter has found applications in real water analysis and for making test strips. Probe2 also showed antibacterial activity against both gram‐positive ( Staphylococcus aureus ) and gram‐negative ( Escherichia coli ) bacteria.